Make or buy, feasibility of intermediate good production - Davis, Mark A. (Kansas State University, 2012)
In the manufacturing process one decision that is common to all industries is the sourcing of intermediate goods used in production. The decision to make internally verses to outsource can affect a firm's comparative advantage and increased company profits. This project deals with sourcing trace minerals used in the production of feed for the commercial production of food animals in the United States. From looking at the sources of minerals to the industry to the current market structure of the trace mineral production industry in the U.S. the question is asked whether trace minerals can be sourced differently for the client to gain this advantage. The specific objective of this research project is to determine whether it is more profitable either to purchase or manufacture trace mineral blends for use in feed ration formulations for a number of plants owned by a representative livestock feed company in western Kansas. The company has several feed plants in operation in the central Great Plains region. Does the company have enough volume of trace mineral usage to enable it to profitably produce its own mineral blends at one of its feed plants? If trace minerals can be profitably produced by the company, it will lead to a decrease in feed production cost for all of its plants. It is possible that this study will show that there is a large enough degree of consolidation in the U.S. mineral blending industry that there is little or no "room" or opportunity available in the competitive raw ingredient market to increase margin by self-producing trace minerals verses outsourcing. The rationale behind this perspective is that the supply of trace mineral blends is controlled tightly by a few existing suppliers / manufacturers who have enough market power and the subsequent ability to limit the entry of new firms. The raw ingredients required to produce these blends could not be purchased economically enough to realize any cost savings in the trace mineral production process.
Keywords: Agribusiness; Livestock; Feed; Feed ingredients; Trace minerals; Logistics